A multi-perspective qualitative study on robotic-assisted surgery training demand - Xinling Tian; Kongying Nong; Xueqi Tang; Jiani Zhai; Yihang Guo; Yueran Li; Yichuan Zhang; Yuzhe Kong; Xiaohong Tang (Scientific Reports)
The increasing popularity of robotic surgery requires surgeons to have higher proficiency in robotic surgery. Currently, there is a conspicuous absence of a unified and standardized curriculum for robotic surgery in China. Considering the pressing necessity to formulate standardized robotic surgery training programs, our objective is to conduct multi-institutional demand assessments. This will enable us to comprehensively discern the requirements of Chinese surgeons regarding training courses for robotic surgery. Semi-structured interviews were conducted in our study. A panel of 41 surgeons from the fields of General Surgery, Gynecology and Urology were included according to the inclusion and exclusion criteria. Based on the grounded theory, the interview data was collected, analyzed and sorted into several aspects. The participants were divided into two groups - teachers and students - based on their prior experience and involvement in robotic surgery. Through a meticulous process of coding and analyzing the interview data, six aspects were identified. These aspects encompassed training necessity, training contents, training methods, potential training evaluation instruments, training duration requirements and training resources. Regarding training necessity, training contents and so on, different groups have basically reached a consensus. Nevertheless, significant discrepancies emerge when identifying the distribution of training durations and the target trainees. This study identified multiple themes across six dimensions related to the curriculum needs of surgeons in robotic surgery. In terms of training content, training methods, etc., the basic viewpoints of teachers and students were the same. However, there were significant differences between the two sides in terms of training duration and training targets. When developing robotic surgery curriculum, these findings are certain to improve the effectiveness and reliability of the courses. They will also optimize the robotic surgical skills of surgeons, thereby reducing complications, infections, etc., and providing good assistance for curing patients.